Notes on Freycinetia (Pandanaceae) from Jambi, Sumatra with the description of a new species - Nursahara Pasaribu; Elizabeth A. Widjaja (REINWARDTIA, 2009)
Nine species of Freycinetia are enumerated for Jambi, Sumatra, Indonesia: F. angustifolia Blume, F. berbakensis Widjaja, Pasaribu & Hidayat, F. imbricata Blume, F. javanica Blume, F. kamiana B.C. Stone, F. rigidifolia Hemsl., F. sumatrana Hemsl., F. winkleriana Martelli and F. scabrosa Pasaribu & Widjaja,. The latest species is newly described. A key to the nine species in Jambi is provided.